2021
DOI: 10.1016/j.ajoc.2020.100998
|View full text |Cite
|
Sign up to set email alerts
|

Central serous chorioretinopathy treatment with a systemic PDE5 and PDE6 inhibitor (sildenafil)

Abstract: Purpose Examine the use of systemic phosphodiesterase inhibition (sildenafil) to clear central serous chorioretinopathy (CSCR). Observations In a long-standing CSCR patient, sildenafil produced a rapid resolution. When discontinued (dechallenge) the CSCR returned. When rechallenged, the CSCR again rapidly disappeared and did not recur in 5 months of continued therapy. Conclusions AND IMPORTANCE: Systemic sildenafil can cause rapid clearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Recently, a study by Breazzano et al in 4 patients with chronic CSCR showed that treatment with sildenafil 40–80 mg twice a daily resolved the subretinal fluid and improved the visual acuity in 2 patients. Moreover, Coleman et al observed that discontinuation of PDE-5 inhibitor determined a recurrence of serous detachment in a patient successfully treated with sildenafil 60 mg daily [ 17 , 18 ]. See Table 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study by Breazzano et al in 4 patients with chronic CSCR showed that treatment with sildenafil 40–80 mg twice a daily resolved the subretinal fluid and improved the visual acuity in 2 patients. Moreover, Coleman et al observed that discontinuation of PDE-5 inhibitor determined a recurrence of serous detachment in a patient successfully treated with sildenafil 60 mg daily [ 17 , 18 ]. See Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…PDE-5 inhibitors are a class of drugs used in erectile dysfunction, lower urinary symptoms, and pulmonary hypertension [10]. Previous studies have hypothesized that sildenafil intake could increase the risk of developing CSCR [11][12][13][14][15] (Table 1); however, a study by French et [17,18]. See Table 2.…”
Section: Discussionmentioning
confidence: 99%